Online degree programmes in nurse education—Students' perceptions and academic performance: An integrative review - Hakkarainen, Tanja; Salminen, Leena; Alastalo, Mika; Virtanen, Heli (Elsevier, 2025)
Objectives: The aim of this integrative review is to identify, describe, and synthesise evidence regarding students' perceptions of online degree programmes in nurse education, their academic performance, and the factors associated with their academic performance.
Design: Integrative review.
Data sources: Four databases, CINAHL, ERIC (Ebsco), PubMed/MEDLINE, and Web of Science were searched. The reference lists of included studies were reviewed to identify other relevant studies.
Review methods: Whittemore and Knafl's method was used as a guideline for the integrative review. Peer-reviewed studies describing students' perceptions of-or academic performance in-online degree programmes in nurse education were included in the review without time limitations. The quality of the selected article was assessed using the Mixed Method Appraisal Tool.
Results: Nursing students' perceptions of online degree programmes were categorised into enabling career development, content delivered online, and community belonging. Factors related to student's academic performance were associated with individual students and the characteristics of online learning environments. Factors associated with students' academic performance were individual self-direction, formal communication skills, and working and educational backgrounds. Factors associated with academic performance in an online learning environment were categorised into regular feedback and methods for learning.
Conclusions: Online degree programmes in nurse education contribute to developing pedagogy through a satisfactory work-life balance, students' experiences of community and support, pleasant digital content, and various teaching methods by faculties. The study findings of this review have implications for educators to develop and adopt strategies for advancing digital environments with the pedagogy that supports community building to meet the needs of individual students.